1861-1862 Wash. Sess. Laws 22, An Act to Incorporate the City of Walla Walla, art. 5, § 3, pt. 22. - (:unkn) unknown (General Publisher, 1862)
To regulate the storage of gunpowder, pitch, tar, rosin and all other combustible materials, . . . in shops, stables and other places. To prevent, remove or secure any fire-place, stove, chimney, oven, boiler, or other apparatus which may be dangerous in causing fire.
--
Keywords: GUN POWDER STORAGE